2010
DOI: 10.1007/s11524-010-9434-8
|View full text |Cite
|
Sign up to set email alerts
|

Why the Wait? Delayed HIV Diagnosis among Men Who Have Sex with Men

Abstract: We sought to identify factors associated with delayed diagnosis of human immunodeficiency virus (HIV; testing HIV-seropositive 6 months or more after HIV seroconversion), by comparing delayed testers to non-delayed testers (persons who were diagnosed within 6 months of HIV seroconversion), in King County, Washington among men who have sex with men (MSM). Participants were recruited from HIV testing sites in the Seattle area. Delayed testing status was determined by the Serologic Testing Algorithm for Recent HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
31
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 18 publications
8
31
0
Order By: Relevance
“…Given the high prevalence of undiagnosed seropositivity, effective evidence-based programs are needed that increase awareness of HIV status among MSM, especially among the subgroups of MSM who are at the greatest risk for not knowing their HIV status, such as MSMW and black/ African American MSM. Offering HIV testing in alternative settings such as bars, parks, and shelters [24] has been suggested for MSM populations that are currently underserved by testing programs in HIV organizations and medical settings. Such populations include lower-income black MSM, MSM who do not have access to care [54], MSM who are non-gay identified [55], and MSMW.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the high prevalence of undiagnosed seropositivity, effective evidence-based programs are needed that increase awareness of HIV status among MSM, especially among the subgroups of MSM who are at the greatest risk for not knowing their HIV status, such as MSMW and black/ African American MSM. Offering HIV testing in alternative settings such as bars, parks, and shelters [24] has been suggested for MSM populations that are currently underserved by testing programs in HIV organizations and medical settings. Such populations include lower-income black MSM, MSM who do not have access to care [54], MSM who are non-gay identified [55], and MSMW.…”
Section: Discussionmentioning
confidence: 99%
“…For example, research suggests that among MSM perception of HIV risk varies by race of partner [21] and by type of partner [22]. Studies have found that perception of risk is associated with HIV testing and delayed HIV diagnosis [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Poor functioning in other areas of sexual health can in fact increase the risk of HIV/STI transmission, as well as adversely affect the detection and outcomes of HIV or STI infection. For example, MSM who are uncomfortable with their sexual orientation or behavior may avoid disclosing same-sex behavior to health care providers or delay HIV/ STI diagnosis and treatment [26][27][28]. An HIV/STI diagnosis can be a marker of the presence of other sexual, mental, or physical health problems (including substance abuse, depression, trauma from physical or sexual abuse, and other co-existing problems) that are associated with sexual dysfunction, risky sexual behavior and higher rates of HIV/STI in MSM [29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…42 Late testing and delayed diagnosis are particularly common among racial/ethnic minority populations. 43,44 In an effort to expand access to HIV testing in the United States, CDC funded demonstration projects to determine the feasibility and effectiveness of using conventional and rapid HIV tests in various clinical and nonclinical settings. 45 Challenges to expanding the scope of HIV testing included competing priorities for limited resources within clinical settings; logistical difficulties testing large numbers of people in clinical and correctional settings; delivering preliminary positive test results in community-based venues and confirmatory results to transient, homeless and other hard-to-reach populations; and linking persons with HIV infection to care in nonclinical settings.…”
Section: Hiv Testing In Clinical and Nonclinical Settingsmentioning
confidence: 99%